4th Flow Control Conference 2008
DOI: 10.2514/6.2008-4311
|View full text |Cite
|
Sign up to set email alerts
|

Successes and Challenges for Flow Control Simulations (Invited)

Abstract: A survey is made of recent computations published for synthetic jet flow control cases from a CFD workshop held in 2004. The three workshop cases were originally chosen to represent different aspects of flow control physics: nominally 2-D synthetic jet into quiescent air, 3-D circular synthetic jet into turbulent boundary-layer crossflow, and nominally 2-D flow-control (both steady suction and oscillatory zero-net-mass-flow) for separation control on a simple wall-mounted aerodynamic hump shape. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Rumsey et al emphasized that there were differences between particle image velocimetry (PIV) and laser Doppler velocimetry (LDV) measurements of the current case in some regions of the flow, and the URANS computations tended to agree better with the LDV data in those regions. In confirmation, all turbulence models by the coarse grid of Rumsey in a normal domain size can capture the general character of the flow. Dandois et al computed the current test case and used both URANS (with Spalart–Allmaras) and large‐eddy simulation (LES) (with a selective mixed‐scale subgrid scale model).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Rumsey et al emphasized that there were differences between particle image velocimetry (PIV) and laser Doppler velocimetry (LDV) measurements of the current case in some regions of the flow, and the URANS computations tended to agree better with the LDV data in those regions. In confirmation, all turbulence models by the coarse grid of Rumsey in a normal domain size can capture the general character of the flow. Dandois et al computed the current test case and used both URANS (with Spalart–Allmaras) and large‐eddy simulation (LES) (with a selective mixed‐scale subgrid scale model).…”
Section: Introductionmentioning
confidence: 69%
“…Although the three investigated turbulence models produced some differences, these differences were generally not too large. Rumsey reported that unsteady RANS (URANS) was particularly unsuccessful to predict turbulence quantities. Rumsey et al emphasized that there were differences between particle image velocimetry (PIV) and laser Doppler velocimetry (LDV) measurements of the current case in some regions of the flow, and the URANS computations tended to agree better with the LDV data in those regions.…”
Section: Introductionmentioning
confidence: 99%
“…The model of the plenum follows one described by Rumsey et al . and Iaccarino et al . The trailing edge of the grid with the plenum is shown in Figure .…”
Section: Methodsmentioning
confidence: 92%
“…Tang and Zhong [17] pointed out that results from the numerical simulation of traditional blowing synthetic jet with the standard k- turbulent model were the closest to the experimental results. Zhang and Wang [18] also used the standard k- turbulent model to simulate the synthetic jet in a quiescent environment, and the results matched quite well with the benchmark experimental data of NASA Langley Research Center [19]. The details of the governing equations and numerical method can be found in the author's previous work [13].…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 58%